2010
DOI: 10.1021/ja104273r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Potential and Temperature Dependences of the Differential Capacitance of a Room-Temperature Ionic Liquid at Graphite Electrodes

Abstract: Molecular dynamics simulation studies of the structure and the differential capacitance (DC) for the ionic liquid (IL) N-methyl-N-propylpyrrolidinium bis(trifluoromethane)sulfonyl imide ([pyr(13)][TFSI]) near a graphite electrode have been performed as a function temperature and electrode potential. The IL exhibits a multilayer structure that extends 20-30 Å from the electrode surface. The composition and ion orientation in the innermost layer were found to be strongly dependent on the electrode potential. Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
372
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(417 citation statements)
references
References 92 publications
(129 reference statements)
42
372
3
Order By: Relevance
“…51 Theoretical studies confirmed the existence of spatial heterogeneities at the interface due to the formation of polar and non-polar domains of the IL-molecules, as well as the existence of highly compressible alternating multilayers. 52,53,54,55,56 At very high negative potentials we could not find ordered superstructures such as those exist on Au(100) in BMIPF6, where ordered double-row structures of the cations could be observed (Fig. 9.…”
Section: In-situ Stmmentioning
confidence: 73%
“…51 Theoretical studies confirmed the existence of spatial heterogeneities at the interface due to the formation of polar and non-polar domains of the IL-molecules, as well as the existence of highly compressible alternating multilayers. 52,53,54,55,56 At very high negative potentials we could not find ordered superstructures such as those exist on Au(100) in BMIPF6, where ordered double-row structures of the cations could be observed (Fig. 9.…”
Section: In-situ Stmmentioning
confidence: 73%
“…Thus, we expect that they will also play a role in establishing the camel shape of the C D . That this is the case, is seen from both simulations (Lamperski & Zydor , 2007;Vatamanu et al , 2010) (Fedorov et al , 2010;Trulsson et al , 2010), play an important role in determining their properties. In this work, we will use a model for ILs wherein the molecular ions interact via dispersion, as well as electrostatic, forces and the cation has an oligomeric structure consistent with imidazolium ions.…”
mentioning
confidence: 67%
“…[19][20][21] In the second cell ('composite electrode', nm. In each of these graphene membranes we carved two holes, each of diameter D=10Å (Fig.…”
Section: Simulation Detailsmentioning
confidence: 99%